Low dose chronicSchistosoma mansoniinfection increases susceptibility toMycobacterium bovisBCG infection in mice - Daniel Eliáš; Hannah Akuffo; Cecilia Thors; A Pawłowski; Sven Britton (2005)
The incidence of mycobacterial diseases is high and the efficacy of Bacillus Calmette Guerin (BCG) is low in most areas of the world where chronic worm infections are common. However, if and how concurrent worm infections could affect immunity to mycobacterial infections has not been elucidated. In this study we investigated whether infection of mice with Schistosoma mansoni could affect the ability of the animals to control Mycobacterium bovis BCG infection and the immune response to mycobacterial antigens. BALB/c mice subclinically infected with S. mansoni were challenged with M. bovis BCG via the intravenous route. The ability of the animals to contain the replication of M. bovis BCG in their organs, lung pathology as well as the in vitro mycobacterial and worm antigen induced immune responses were evaluated. The results showed that S. mansoni coinfected mice had significantly higher levels of BCG bacilli in their organs and sustained greater lung pathology compared to Schistosoma uninfected controls. Moreover, Schistosoma infected mice show depressed mycobacterial antigen specific Th1 type responses. This is an indication that chronic worm infection could affect resistance/susceptibility to mycobacterial infections by impairing mycobacteria antigen specific Th1 type responses. This finding is potentially important in the control of TB in helminth endemic parts of the world.